Numerical Study of Savo-Mod F-30 Three Bladed Vertical Shaft Wind Turbine - Fauziah Khofifah; Ahmed S. AlJarakh; M. Kahrom (Journal Electrical and Computer Experiences, 2026)
Wind turbines are one of the media that can convert wind energy into electrical energy. The vertical axis of the Savonius wind turbine is a type of turbine that can operate well at changing wind speeds and directions. The aerodynamic shape is a factor that affects the performance of this wind turbine. This research was conducted using the CFD method with the help of CATIA, Gambit, and Fluent software. The design of the modified Savonius wind turbine design has 3 blades and is given four TSR variations as well as four wind speed variations which help in finding comparisons in simulation results. The results of the simulation are the aerodynamic force coefficient, power, and torque moment of the three-blade Savonius turbine numerically studied in three dimensions.